Entre laços e memórias: processos de afirmação e reconhecimento étnico enquanto remanescente de quilombo na comunidade do São Francisco no rio Bauana/AM - Oliveira, André Souza de (2022)
The present research investigated the processes of ethnic affirmation and recognition and the struggle of the São Francisco community on the Bauana Tefé/Am river, as a quilombo remnant. Currently, this community is going through a complex process; on the one hand, there is a struggle for the recognition of the community as a quilombola, on the other hand, some community members are opposed to this process. The purpose of the work was to unveil this process. In order to answer them, we used a qualitative approach, the SnowBall Sampling (Snowball) recruitment method, which uses reference chains and the semi-structured interview technique (via telephone) remotely and in person and unsystematic observation. The applied questions were directed to the process of affirmation and ethnic recognition in the community and the manifestations of the black culture. The research had 23 interviewees from diverse segments such as teachers, farmers, health agents and the president of the community, in addition to six (06) informants. We followed this path from an interdisciplinary perspective, both through oral history and anthropology. As for the theoretical discussion, we have the main authors such as Gomes (2015), Arruti (2006), Almeida (2002), Leite (2000), O'Dwyer, who approach the topic in a systematic way, providing the scientific text with subsidies for analysis. of the search results. The results showed that the São Francisco community participates in a cultural entanglement as an Afro-descendant, in the face of this, it has sought recognition as a quilombo remnant, although it has been confirmed that a family did not appreciate the same purpose. The research also identified that the community members were unaware of the rights and benefits involved in achieving this recognition and that the existing conflicts were in the lack of assertive information despite the process with the competent body.